Chemical characterization and anti-hyperglycaemic effects of polyphenol enriched longan (Dimocarpus longan Lour.) pericarp extracts. (March 2015) - Li, Liya; Xu, Jialin; Mu, Yu; Han, Li; Liu, Ruohan; Cai, Yaping; Huang, Xueshi
Highlights: Longan pericarp extracts reduce postprandial hyperglycaemia by inhibiting α-glucosidase in the gut lumen. Longan pericarp extracts enhance mouse glucose tolerance with short-term oral administration. Longan pericarp extracts enhance insulin sensitivity via increasing Irs-1, Pparγ and Glut4 gene expression. Abstract: The chemical composition and anti-hyperglycaemic effects of polyphenol-enriched Longan pericarp extracts (LPE) were investigated in the present study. The phenolic profile of LPE was determined by HPLC-DAD/MS analysis. Nine phenolics were identified, and of these, three major components were quantified by LC-MS/MS. Anti-hyperglycaemic assays demonstrate that LPE (polyphenol content ca. 37.8 g gallic acid equivalents/100 g) inhibit α-glucosidase (IC50  = 11.68 ± 0.44 µg/mL) in vitro and decrease blood glucose content in mice (P < 0.05) upon sucrose challenge. In addition, LPE improves mouse glucose tolerance following 5 days of treatment by oral gavage (10 mg/kg body weight), which may be due to the increased gene expression associated with insulin signalling pathway, such as insulin receptor substrate-1, peroxisome proliferator-activated receptor γ and glucose transporter 4. Overall, our results suggest that LPE could impact carbohydrate metabolism and enhance insulin sensitivity and may serve as a potential anti-hyperglycaemic agent in diabetes care.